The Influence of Product Quality and Brand Image on Shell Fuel Consumers’ Purchasing Decision in Surabaya - Radithya Satria Wardhana; Zumrotul Fitriyah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to identidy and examine how people’s views on product quality and brand image affect their decision to buy Shell fuel in Surabaya City. The study fecoses on three key areas: first, how both product quality perception and brand image together influence purchase decisions; second, how product quality perception alone impacts purchase decisions; and third, how brand image alone affects purchase decisions. The group of people studied are those who buy and use Shell fuel in Surabaya. To select participants, a non-probability sampling method was used, with the criteria that respondents must be at least 17 years old, live in Surabaya, and have purchased Shell fuel. After distributing questionnaires, 100 people met these criteria. The data was analyzed using Partial Least Squares-Structural Equation Modelling (PLS-SEM) with SmartPLS 3.0 software. The findings show that both product quality perception and brand image together have a significant effect on purchase decisions. Individually, product quality perception has a positive and significant impact on purchase decisions, and brand image also shows a positive and significant effect. These results suggest that improving product quality and enhancing brand image can help Shell increase consumer purchase decisions in Surabaya.